Electromagnetic Wave Absorption Efficiency Of Green Superhydrophobic Magnetic Nanocomposite Sheet From Durian Shell - Arif, Afraha Baiti (2019)
Electromagnetic (EM) wave absorbers are specifically designed materials that can inhibit the reflection or transmission of EM radiation. The increasing numbers in electronic and telecommunication devices has created electromagnetic interference (EMI) in which leads to application disturbance. Thus, the use of EM wave absorber with the ability of high absorption is strongly in demand. Current magnetic sheets are made from polymer-based materials; however, it takes decades to degrade and cause pollution. Thus, the use of natural fibres in replacing polymer is strongly encouraged. However, cellulose sources are highly hygroscopic. As a result, it loses its important mechanical attributes and affects the quality of the magnetic sheet. In this study, a novel superhydrophobic EM wave absorber of thin, light weight, flexible, green and low cost magnetic nanocomposite sheet that function in high frequency range was fabricated. Here, durian shell (Durio zibethinus Murray) from D24 variety was explored to examine its hydrophobic behaviour and compatibility as a magnetic sheet matrix. The chemical composition, surface functional groups, thermal stability and cross section morphology of the fibre were characterised. The process conditions of soda pulping were optimised using a two-level factorial design in order to achieve the optimum amount of lignin that can give the highest water contact angle among the produced durian shell composite sheets. The percentage of alkalinity, cooking temperature and cooking period are the most affected factors to the model. Mechanical properties such as tensile, tear, burst and folding endurance of the composite sheets decreased as the amount of lignin increasing. For embedding magnetic nanoparticles inside the fibre lumen phase, the lumen loading method had a better magnetic loading and magnetization compared to the in situ. Vibrating sample magnetometer (VSM) data shows that the durian shell wave absorbers exhibited good superparamagnetic behaviour. The existence of the magnetic nanoparticles was confirmed with X-ray diffraction (XRD), scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDS) mapping and X-ray photoelectron spectroscopy (XRD) analysis. Optimisation of lumen loading process conditions was carried out via face-centred central composite design (FCCD) to obtain the highest magnetisation property. In overcoming the hygroscopic behaviour of cellulose, three coating techniques have been employed; dip coating using stearic acid, blending polymer via disintegration method and drop coating using modified silica particles. Dip coating using stearic acid was selected as the best technique as the water contact angle produced exceeds 150°. Cobb test was carried out to check the water absorptiveness of the coated magnetic sheet. The performance of EM wave absorber was tested using vector network analyzer (VNA) through the reading of reflection loss, permittivity and permeability of the samples in the 4-18 GHz frequency range. All the samples were also tested for the ultra-high frequency of radio frequency identification (UHF RFID) reading distance in metallic environment. The results obtained showed that the green superhydrophobic magnetic nanocomposite sheet has a better performance in alleviating the EMI problem.